Identification of Novel Risk Loci for Behçet's Disease–Related Uveitis in a Chinese Population in a Genome‐Wide Association Study. Issue 4 (14th February 2022) - Su, Guannan; Zhong, Zhenyu; Zhou, Qingyun; Du, Liping; Ye, Zi; Li, Fuzhen; Zhuang, Wenjuan; Wang, Chaokui; Liang, Liang; Ji, Yan; Cao, Qingfeng; Wang, Qingfeng; et al.
Abstract : Objective: To explore susceptibility loci associated with uveitis in Behçet's disease (BD). Methods: We conducted a 2‐stage study, consisting of a genome‐wide association study (GWAS) stage and a replication stage, in a Chinese population. The GWAS stage included 978 cases with BD‐related uveitis and 4, 388 controls, and the replication stage included 953 cases with BD‐related uveitis and 2, 129 controls. Luciferase reporter analysis and chromatin immunoprecipitation assay were performed to explore the functional role of susceptibility genetic variants near ZMIZ1. Results: Three independent HLA alleles (HLA–B51 [3.75 × 10 −190 ], HLA–A26 [1.50 × 10 −18 ], and HLA–C0704 [3.44 × 10 −16 ]) were identified as having a genome‐wide association with BD‐related uveitis. In the non‐HLA region, in addition to confirming 7 previously reported loci, we identified 22 novel susceptibility variants located in 16 loci. Meta‐analysis of the Chinese cohort consisting of 1, 931 cases and 6, 517 controls and a published Japanese cohort of 611 cases and 737 controls showed genome‐wide significant associations with ZMIZ1, RPS6KA4, IL10RA, SIPA1‐FIBP‐FOSL1, and VAMP1. Functional experiments demonstrated that genetic variants of ZMIZ1 were associated with enhanced transcription activity and increased expression of ZMIZ1. Conclusion: This GWAS study identified a novel set of genetic variants that are associated with susceptibility to uveitis in BD. These findings enrich our understanding of the contribution of genetic factors to the disease.